الجملة الاسمية في سورة البقرة: دراسة نحوية تطبيقية - عويقب, فتيحة (جامعة الوادي - University of Eloued, 2022)
تهدف هذه الورقة البحثية إلى الوقوف على أهم الجمل الاسمية التي ورد ذكرها في سورة البقرة-التي تعد أطول سورة في القرآن الكريم-مع تتبع مواطن التقديم والأخير، الذكر والحذف...وكل التغيرات التي طرأت عليها، وتبيان الغرض من ذلك في كل حالة. فقد وقفنا على الكثير من الشواهد التي وجدناها متوفرة في سورة البقرة، وذلك بإعرابها إعرابا مفصلا يخص الجملة الاسمية بالإضافة إلى الإشارة في بعض الأحيان إلى دلالة بعض اللآيات ورأي بعض المفسرين حولها. وفي الأخير تبين لنا سورة البقرة كانت مثالا حيًّا عن جلّ الشواهد التي تتعلق بالجملة الاسمية، وما يطرأ على ركنيها من تغيير يدلّ في كل مرّة على الإعجاز القرآني. Abstract : This research paper aims to stand on the most important nominal sentences mentioned in Surat Al- Baqarah, which is the longest Surah in the Holy Qur’an, while tracking the places of introduction and delay, mention and delete…and all the changes that occurred in nominal sentences, and clarifying the purpose of that in each case. We have come across many of the evidence that we found available in Surat Al- Baqarah, by translating it into a detailed parsing concerning the nominal sentences, in addition to sometimes referring to the significance of some verses and the opinion of some exegetes about them. In the end, Surat Al-Baqarah was a living example of most of the evidence related to the nominal sentence, and the change that occurs to its corners, which indicates each time the Qur’anic miracle. Keywords: Sentence; Nominal; Surat Al-Baqarah ; Applied study; Grammar.
The Nominal Sentence in Surat Al-Baqarah -An Applied Grammatical Study-
مقال
Keywords: الجملة الاسمية؛ سورة البقرة؛ دراسة تطبيقية؛ النّحو; Sentence Nominal; Surat Al-Baqarah ; Applied study; Grammar.